2018
DOI: 10.1016/j.foodchem.2017.11.120
|View full text |Cite
|
Sign up to set email alerts
|

Determination of free, esterified, glycosylated and insoluble-bound phenolics composition in the edible part of araticum fruit (Annona crassiflora Mart.) and its by-products by HPLC-ESI-MS/MS

Abstract: Phenolics present in the free, esterified, glycosylated and insoluble-bound forms of araticum pulp, peel and seed were for the first time characterized and quantified using HPLC-ESI-MS/MS. Levels of total phenolics, flavonoids, condensed tannins and antioxidant activities from araticum fruit followed the order peel > pulp > seed. Overall, insoluble-bound and esterified phenolics were the dominant forms of phenolics from araticum fruit parts and the highest contributors to their antioxidant activities. Extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
77
5
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(98 citation statements)
references
References 42 publications
13
77
5
3
Order By: Relevance
“…Several pieces of evidence have demonstrated that different plant parts may present different phenolic compounds [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ], therefore suggesting that the expression of genes associated with the production of some enzymes may be tissue specific. Likewise, not only the absorption of the phenolics is important but also their structure/activity [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several pieces of evidence have demonstrated that different plant parts may present different phenolic compounds [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ], therefore suggesting that the expression of genes associated with the production of some enzymes may be tissue specific. Likewise, not only the absorption of the phenolics is important but also their structure/activity [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 14 compounds were tentatively identified based on molecular ions, retention time, major fragment ions, online databases and published articles. The details of the identified compounds are listed in Table 1 15 19 .
Figure 2 MS chromatograms of TTS.
…”
Section: Resultsmentioning
confidence: 99%
“…The nutraceutical functional oil, for example sunflower oil, contains unsaturated fatty acids, vitamin E, antioxidants tocopherols and tocotrienols, phytosterols, phenolics, carotenoids, and chlorophylls. The nutraceutical features of common oilseed crops have been reported (Arruda, Pereira, de Morais, Eberlin, & Pastore, 2018). Better still, the current awareness about the continuous use of synthetic pharmaceuticals in phytomedicines and extraction natural functional oil from plants as an alternative could help in proffering curable solutions to various diseases affecting humans (Maqsood, Adiamo, Ahmad, & Mudgil, 2020).…”
Section: Benefits Of Sunflowermentioning
confidence: 98%